Moral Values in the Eid Al-Fitr Tradition in Kotorajo District, Kuantan Hilir Seberang District Kuantan Singingi Regency - Juswandi, Juswandi; Hermansyah, Hermansyah; Amanan, Amanan (Universitas PGRI Sumatera Barat, 2023)
This research aims to determine the moral values in the Eid al-Fitr tradition in Kenegerian Kotorajo, Kuantan Hilir Seberang District, Kuantan Singingi Regency, Riau. The method used in this research is qualitative method. The data collection techniques used were observation, interviews and documentation. The data analysis used is by reducing the data obtained in the field and then presenting the data in the form of descriptions or describing and interpreting Eid traditional objects in Kenegerian Kotorajo, Kuantan Hilir Seberang District, Kuantan Hilir Regency. And verify the data according to the research results found. The results of this research show that the Eid tradition carries out various activities carried out in general by both men and women, small and large people, even from children to the elderly. This activity begins on the evening of takbiran, after the Isha prayer they go around the village on foot starting from the mosque or surau and ending back at the mosque. Then in the morning perform the Eid prayer/Eid prayer. Then they returned home, some stopped at neighboring houses. Next, get ready to go to the grave or cemetery. Then go to the godang house or tribal house. Then for the next three days there will be pencak silat games. From this series of traditional activities, there are moral values contained in the relationship between living creatures and the creator, the relationship with the environment, mutual friendship, greeting each other, etiquette, the Eid tradition is one way to maintain friendship carried out by the community by walking. together around the village and at the same time forgiving the people who had been waiting along the road. Next, the value of grave pilgrimage is: 1). The Value of Being Thankful to Allah, 2). The Value of Praying to Allah and 3). The Value of Charity. Religious values are solidarity values, moral values, artistic values and now these values are increasing with economic values.